LETTERING BOOK FOR SPECIAL-NEEDS AND LOW-LEVEL PRIMARY SCHOOL STUDENTS - Zulfian Rahman; Ikhsanudin Ikhsanudin; Sudarsono Sudarsono (ICoTE Proceedings, 2019)
This article initiates the discussion about alternative idea that might break the deadlock in supporting materials for students with writing difficulty in inclusive school and children with special needs in general. This article discuss the importance of lettering book and alternatives in order to help children to overcome their weaknesses in learning basic skills such as writing. In this article, the writer includes introduction, types of special needs and low-level primary school students, the definition of lettering, parenting for helping the special needs children, and conclusion. Furthermore, the book can be used by teacher and parents outside the classroom to direct children’s activity and to control their progress in the remedy of their learning disabilities. In the last part, the writer urges publishers and teachers to develop lettering book for children with special needs to overcome the children’s difficulty in acquiring writing skills.